ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP CARA PEMBUANGAN LIMBAH MEDIS PADA PASIEN DIABETES MELITUS TIPE 2 YANG MENGGUNAKAN TERAPI INSULINDI RSUP FATMAWATI - Hafidz Naeriansyah Djajawiguna (2020)
Inappropriate disposal of insulin syringes in people with type 2 diabetes mellitus will pose an risk of infection and environmental hazards for individuals and the community. The way to dispose syringe waste can be influenced by several factors such as age, sex, education status, employment status, duration of diabetes mellitus, duration of insulin therapy and education given to patients. This study was aimed to determine the factors that influence the way to dispose medical waste in patients with moderate type 2 diabetes mellitus using insulin therapy. This research was an analytical observational with cross-sectional design. The sampling technique used consecutive sampling. There were 103 participants. Data was collected at Fatmawati General Hospital using disposal behavior of insulin syringe waste Questionnaire. There is a significant relationship between educational status and disposal behavior of insulin syringe waste (p = 0.014). Education status is the most influential factor (OR: 3.333). There is a significant association between educational status and disposal behavior of insulin syringe waste with education status as the most influential factor that affects disposal behavior of insulin syringe waste. The higher patient's education status, the better behavior of insulin syringe disposal.